The Maternally Inheritable Wolbachia wAlbB Induces Refractoriness to Plasmodium berghei in Anopheles stephensi - Joshi, Deepak (Front Microbiol, 2017)
The endosymbiont Wolbachia wAlbB induces refractoriness to Plasmodium falciparum in Anopheles stephensi, the primary mosquito vector of human malaria in the Middle East and South Asia. However, it remains unknown whether such refractoriness can be extended to other malaria species. In particular, it was reported that under very specific conditions, wAlbB can enhance Plasmodium infection in some hosts. Here, we measured the impact of wAlbB on the rodent malaria parasite Plasmodium berghei in A. stephensi by comparing the load of oocysts and sporozoites in midguts and salivary glands, respectively, between wAlbB-infected and -uninfected mosquitoes. To investigate whether wAlbB modulated mosquito immune defense against parasites, we compared the expression of the immune genes, which were previously reported to involve in antimalarial response, in both midguts and the remaining carcass tissues of mosquitoes. The stable association of wAlbB with A. stephensi resulted in reduction of parasites by more than half at the oocyst stage, and up to 91.8% at the sporzoite stage. The anti-plasmodium immune genes, including TEP1, LRIM1, Toll pathway gene Rel1 and the effector Defensin 1, were induced by wAlbB in different mosquito body tissues. These findings suggest that immune priming is a potential cause of wAlbB-mediated antimalarial response in A. stephensi. More importantly, no evidence was found for any enhancement of Plasmodium infection in A. stephensi stably infected with wAlbB. We discuss these findings with possible implementations of Wolbachia for malaria control in disease endemic areas.